Torque and power about the joints of the arm during the freestyle stroke - Harrison, S. M.; Cohen, R. C. Z.; Clearly, P. W.; Mason, B. R.; Pease, D. L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Improvement of swimming performance involves changes to technique, endurance and strength, but the relationship between these factors cannot be predicted precisely for an individual athlete. Recent advances in computational models of swimming provide the opportunity to study these relationships in a virtual environment. Unlike in physical experimentation, the forces on individual body segments, torque about body joints and joint powers can be calculated in the model. These model outputs allow new insight into the loading on the body from the fluid along with the internal biomechanical forces that result. We use a coupled Biomechanicai-Smoothed Particle Hydrodynamics (B-SPH) model to calculate joint torque and joint powers for the arms of a male elite athlete performing a freestyle stroke. Results show the large demand on the muscles of the arm, especially those spanning the shoulder. Future developments and applications of the model are discussed.